A rare presentation of enterocutaneous fistula - Thirunavukkarasu, Devi; Khanna, Sriram; Swaminathan, Shanthi Ponnandai; Kannan, R. (International Surgery Journal, 2022)
Enterocutaneous fistula is an abnormal communication between two epithelialized surfaces, one of which is a hollow viscous organ. It most commonly occurs as a surgical complication. Other causes are trauma, malignancy, inflammatory bowel disease, ischemia. The great majority of enterocutaneous fistula are iatrogenic (75-85%) and rest (15-25%) occur spontaneously. Enterocutaneous fistula is the one of the most challenging conditions managed by General surgeon. The mortality rates vary in different series for patients, with enterocutaneous fistula and remains 5% to 15%.Here we report a rare presentation of enterocutaneous fistula.